2018
DOI: 10.1055/s-0038-1636931
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Subjective and Objective Outcomes and Return to Play in Anterior Cruciate Ligament Reconstruction: A Retrospective Cohort Study

Abstract: Purpose  To analyze the prognostic factors influencing subjective and objective outcomes and return to play (RTP) after anterior cruciate ligament reconstruction (ACL-R). Methods  Primary ACL-Rs using a transtibial technique performed between 2008 and 2012 were included. Data regarding patients, surgery, sports, and rehabilitation, including an on-field rehabilitation (OFR) and duration of the rehabilitation program, were collected. The International Knee Documentation Committee (IKDC) subjective and objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…All studies compared a group of patients who completed a shorter duration of supervised rehabilitation (less than 3 or 6 months) to a group of patients who completed six or more months of rehabilitation, including structured agility, gym exercises, landing and on-field rehabilitation in line with current evidence-based recommendations Supervised rehabilitation longer than 6 months was associated with improved outcomes at all assessment time points. Specifically, associations were found between longer supervised rehabilitation and functional symmetry [50,51], a greater likelihood of meeting return to sport criteria and RTS at 12 months [50,51], double leg vertical hop landing symmetry [52,53], knee flexor rate of torque development and symmetry [54], speed and agility [55], knee extensor muscles torque parameters and LSI values [56] and better subjective outcomes [57]. Delaying the start of rehabilitation longer than one month after reconstruction was negatively associated with objective outcomes [57].…”
Section: Supervised Rehabilitation Duration Original Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies compared a group of patients who completed a shorter duration of supervised rehabilitation (less than 3 or 6 months) to a group of patients who completed six or more months of rehabilitation, including structured agility, gym exercises, landing and on-field rehabilitation in line with current evidence-based recommendations Supervised rehabilitation longer than 6 months was associated with improved outcomes at all assessment time points. Specifically, associations were found between longer supervised rehabilitation and functional symmetry [50,51], a greater likelihood of meeting return to sport criteria and RTS at 12 months [50,51], double leg vertical hop landing symmetry [52,53], knee flexor rate of torque development and symmetry [54], speed and agility [55], knee extensor muscles torque parameters and LSI values [56] and better subjective outcomes [57]. Delaying the start of rehabilitation longer than one month after reconstruction was negatively associated with objective outcomes [57].…”
Section: Supervised Rehabilitation Duration Original Studiesmentioning
confidence: 99%
“…Specifically, associations were found between longer supervised rehabilitation and functional symmetry [50,51], a greater likelihood of meeting return to sport criteria and RTS at 12 months [50,51], double leg vertical hop landing symmetry [52,53], knee flexor rate of torque development and symmetry [54], speed and agility [55], knee extensor muscles torque parameters and LSI values [56] and better subjective outcomes [57]. Delaying the start of rehabilitation longer than one month after reconstruction was negatively associated with objective outcomes [57]. However, the duration of supervised rehabilitation was not associated with one leg vertical hop symmetry [53], knee joint stability, thigh and knee joint circumferences, active range of motion or everyday pain [55].…”
Section: Supervised Rehabilitation Duration Original Studiesmentioning
confidence: 99%
“…Among various treatment options, ACL reconstruction has become the top choice of orthopedics doctors, for ligament reconstruction could help patients re-obtain relatively normal knee function and potentially delay consequent osteoarthritis [ 2 4 ]. It has been estimated that there are 329–435 per 1 000 000 person each year from 1994 to 2006 who receive ACL reconstruction in the United States [ 5 ]. Although numerous studies have reported excellent subjective and objective outcomes after ACL reconstruction, satisfactory results require careful postoperative nursing and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest New Zealanders are not receiving physiotherapy treatment for an appropriate duration following ACL injury or surgery. Post-ACLR rehabilitation lasting up to 12 months is associated with improved knee flexor/extensor strength (Ageberg, Thomeé, Neeter, Silbernagel, & Roos, 2008;Heijne & Werner, 2007;, greater performance during functional testing , a greater rate of returning to pre-injury activities (Ardern et al, 2014;Della Villa et al, 2012;Edwards et al, 2018;Han et al, 2015;Rosso et al, 2018) and decreased re-injury risk (Grindem, Snyder-Mackler, Moksnes, Engebretsen, & Risberg, 2016). Traditional progressions through ACL rehabilitation have been time based, which may result in sub-optimal outcomes, as time after ACLR is not necessarily related to functional performance (Myer et al, 2012).…”
Section: Duration and Quantity Of Physiotherapy Treatmentmentioning
confidence: 99%
“…Early physiotherapeutic intervention after ACL injury, including education about the importance of rehabilitation, could positively influence the patient experience and may increase adherence to rehabilitation Risberg et al, 2016;Scott et al, 2018). Increased adherence to rehabilitation is positively associated with functional ability following ACLR (Brewer et al, 2000;Pizzari, Taylor, McBurney, & Feller, 2005;Rosso et al, 2018).…”
Section: Duration and Quantity Of Physiotherapy Treatmentmentioning
confidence: 99%